Thematic representation of audiovisual material in multimedia repositories of Brazilian federal institutions: a case study with a paradigmatic concept - Assuncao, Suelene Santana; Diniz, Joao Vitor Correa; Redigolo, Franciele Marques; Fujita, Mariangela Spotti Lopes[UNESP] (Univ Zaragoza, 2022)
The thematic representation of audiovisual material in multimedia repositories is explored throughout a case study with a paradigmatic concept for Brazil: 'Amazonia'. Three multimedia repositories of Brazilian federal institutions were researched for videos on the topic: the LUME repository, hosted in a domain of the Federal University of Rio Grande do Sul (UFRGS); the Institutional Repository of Geosciences of the Mineral Resources Research Company (CPRM), known as RIGeo; and the Multimedia Repository of the Federal University of Para (UFPA). 27 results were retrieved in UFPA, 2 in LUME rand none in RIGeo. It was found that the analyzed repositories use up to ten general and specific terms for the thematic representation of an audiovisual document in video format. Paradoxically, such an important concept for Brazil is not always easily retrieved in relevant audiovisual repositories, which highlights the importance of a proper thematic representation in these databases.
Keywords: Thematic indexing; Institutional repositories; Multimedia; Audiovisual documents; LUME Repository (Brazil); Institutional Repository of Geosciences of the Mineral Resources Research Company (Brazil); UFPA Multimidia Repository (Brazil); Amazon; Brazil